IMPLEMENTATION OF BASIC DATA APPLICATION OF EDUCATION (DAPODIK) IN DATA COLLECTION OF BASIC EDUCATION PRINCIPAL (DAPODIKNAS) AT SD INPRES BARRU 1 BARRU DISTRICT BARRU REGENCY - Muhammad, Mukmin; Mahmud, Usamah; Firdaus, Fitriani Fitriani (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal